2017
DOI: 10.7759/cureus.1640
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Meningioangiomatosis: A Series of Three Pediatric Cases

Abstract: Meningioangiomatosis (MA) is a rare benign, hamartomatous lesion within the leptomeninges and cerebral cortex. Three percent of intractable epileptic patients with tumor develop MA. It may be accompanied with neurofibromatosis type II, or it may occur sporadically.Three patients, age range of 2-16 years old, presented with episodes of seizure. The patients demonstrated no family history or stigmata of neurofibromatosis type II. Electroencephalogram (EEG) was unremarkable for epileptiform activity. Magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For instance, Lucila Domecq Laplace et al [ 27 ] reported three cases of CAPNON located in the posterior fossa with perilesional edema, and the vast majority were cured after total resection. However patients may experience recurrence because of incomplete evacuation [ 28 ], neoplastic malignancy [ 12 ], or coexisting with other malignant tumors [ 20 , 21 ]. In addition to surgery, medical treatment and follow-up observations have been reported [ 1 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lucila Domecq Laplace et al [ 27 ] reported three cases of CAPNON located in the posterior fossa with perilesional edema, and the vast majority were cured after total resection. However patients may experience recurrence because of incomplete evacuation [ 28 ], neoplastic malignancy [ 12 ], or coexisting with other malignant tumors [ 20 , 21 ]. In addition to surgery, medical treatment and follow-up observations have been reported [ 1 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, limited understanding of characteristic clinical manifestations complicates the distinction between MA and MA-M, making clinical diagnosis complex. A review of related literature revealed that MA is often associated with a hypointense region on T1-weighted MRI and a hyperintense area on T2-weighted images, whereas contrast-enhanced MRIs usually demonstrate irregular or homogeneous enhancement ( 7 ). This case report is consistent with these findings, suggesting that the possibility of MA should be considered when differentiating between calcified lesions or meningeal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment has become the first therapeutical option, and a gross total resection is associated with favorable long-term outcomes. However, it is not technically easy to achieve these results, as surgical risks are considerable and serious complications have been reported 17,18 . Chemo and radiotherapy must be considered but must not be overused, as this diagnosis tends to be mistaken for malignant meningiomas.…”
Section: Discussionmentioning
confidence: 99%